Detection des ondes élastiques dans les matériaux piézoéléctriques - منال, عبيد; هناء, عماري (University Of El Oued, 2020)
" This work focuses on the field of acoustic microwaves that propagate in piezoelectric devices. In this case the information circulates in an elastic aspect, that aspect, which is not Sensitive to noise, allows to improve the performance of these devices especially at the level of parasites and the stability of the systems for high frequencies. The objective of our work is to detect elastic waves in solids, explaining their generation and propagation in piezoelectric materials as well as their excitation by interdigitated transducers. The study focused on two piezoelectric materials which are the Niobate Lithium and Lithium Tantalate. We briefly explained the phenomenon of elastic detection in a piezoelectric crystal followed by a comparison of the results obtained at the level of the two crystals. " "يركز هذا العمل عى مجال الموجات متناهية الصغر الصوتية التي تنتشر في الأجهزة الكهربائية التي تعمل بالكهرباء. وفي هذه الحالة، يتم تداول المعلومات في جانب مرن، وهذا الجانب، الذي لا يتأثر بالضوضاء، يسمح بتحسين أداء هذه الأجهزة، خاصة عند مستوى الطفيليات واستقرار أنظمة الترددات العالية. الهدف من عملنا هو اكتشاف الموجات المرنة في المواد الصلبة، عن طريق شرح توليدهم وانتشارهم في المواد الكهرو ضغطية وكذلك إثارتهم بواسطة محولات الطاقة بين الأصابع ركزت الدراسة على مادتين تعملان بالكهرباء الانضغاطية وهما نيوباتي الليثيوم والليثيوم تنتاليت. شرحنا بإيجاز ظاهرة الكشف عن المرونة في بلورة كهرو ضغطية متبوعة بمقارنة بين النتائج المتحصل عليها على مستوى البلورتين "
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: Piezoelectric Materials, Surface Waves, Volume Waves, Leakage Waves, Acoustic microwaves.; " الموجات الدقيقة الصوتية ، موجات السطح ، موجات الحجم ، موجات التسرب ، مواد كهرو ضغطية "